Handbook of research on military expenditure on economic and political resources - Das, Ramesh Chandra 1973 (Information Science Reference, an imprint of IGI Global, 2018)
"This book explores the causal link between GDP and military expenditure, and other economic and political indicators of the countries of different status of developments for the period of formal wars to till date. It surveys the interdependences between the national output and military or defense expenditure and provides an updated progress in the present research arena"